2019
DOI: 10.1038/s41598-019-39568-6
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of pathogenesis-related proteins in transplastomic tobacco plants confers resistance to filamentous pathogens under field trials

Abstract: Plants are continuously challenged by pathogens, affecting most staple crops compromising food security. They have evolved different mechanisms to counterattack pathogen infection, including the accumulation of pathogenesis-related (PR) proteins. These proteins have been implicated in active defense, and their overexpression has led to enhanced resistance in nuclear transgenic plants, although in many cases constitutive expression resulted in lesion-mimic phenotypes. We decided to evaluate plastid transformati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(30 citation statements)
references
References 82 publications
2
28
0
Order By: Relevance
“…An accumulation of PR proteins, such as GLU, is stimulated by J [37], which was mainly proved by our experiments with inoculated and non-inoculated treatments. Generally, we showed a lower GLU activity after inoculation with a non-pathogenic bacterial isolate, which is in line with the finding that its enhanced activity resulted in intensified resistance against pathogens [51].…”
Section: Discussionsupporting
confidence: 89%
“…An accumulation of PR proteins, such as GLU, is stimulated by J [37], which was mainly proved by our experiments with inoculated and non-inoculated treatments. Generally, we showed a lower GLU activity after inoculation with a non-pathogenic bacterial isolate, which is in line with the finding that its enhanced activity resulted in intensified resistance against pathogens [51].…”
Section: Discussionsupporting
confidence: 89%
“…Overexpression of GmDR1 transgenes induced constitutive overexpression of GmPR1‐1 ( Glyma.15g062500 ), but not GmPR1‐2 ( Glyma.13G251600 ), in roots of transgenic lines (Figure 2e,f). Earlier studies have showed that overexpression of PR1 enhances resistance against both bacterial and fungal pathogens (Alexander et al ., 1993; Breen et al ., 2017; Sarowar et al ., 2005; Shin et al ., 2014) suggesting the role of antimicrobial activities of the PR1 proteins in plant defences (Boccardo et al ., 2019; Chen et al ., 2014; Leah et al ., 1991; Selitrennikoff, 2001). It is also known that PR1 proteins interact with pathogen effectors (Breen et al ., 2017; Breen et al ., 2016; Lu et al ., 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Many toxins and defensive proteins are commercially important. For example, plant toxins such as defensin-like protein, animal toxins such as cecropin are used to develop disease-resistant transgenic crops (Stotz et al ., 2009; Lacerda et al ., 2014; Wu et al ., 2016; Pathogenesis-related proteins and peptides as promising tools for engineering plants with multiple stress tolerance, 2018; Boccardo et al ., 2019). Similarly, the cytotoxic activity of phospholipase A2 on cancer cells makes it a promising candidate for cancer therapy (Xiao et al ., 2017; Hiu and Yap, 2020; Lomonte and Rangel, 2012).…”
Section: Discussionmentioning
confidence: 99%